2022
DOI: 10.1039/d2ay00682k
|View full text |Cite
|
Sign up to set email alerts
|

Simple synthesis of green luminescent N-doped carbon dots for malachite green determination

Abstract: In this paper, novel N-doped carbon dots (N-CDs) were prepared from fuchsin basic and ethylenediamine tetraacetic acid disodium salt (EDTA-2Na). The N-CDs were characterized by a series of techniques and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The results of UV-Vis absorption spectroscopy tests performed on it ( Figure S3a ) showed that an absorption peak near 215 nm could be attributed to a π-π* leap in the C=C bond [ 32 , 33 , 34 ]. In contrast, the absorption near 345 belongs to the n-π* leap of C=O/C=N [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of UV-Vis absorption spectroscopy tests performed on it ( Figure S3a ) showed that an absorption peak near 215 nm could be attributed to a π-π* leap in the C=C bond [ 32 , 33 , 34 ]. In contrast, the absorption near 345 belongs to the n-π* leap of C=O/C=N [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%